School guidance and counselling : trends and practices - Luk-Fong, Pattie Yuk Yee; Lee-Man, Yuk Ching (Hong Kong teacher education., 2013)
This book provides a comprehensive introduction to school guidance and counselling services in Hong Kong. It draws extensively on current research in the field, with a special emphasis on how guidance and counselling could be systematically planned to meet the personal, social and educational and career needs of students. The chapters discuss how counselling could be infused into school activities by employing a team approach, wherein all staff members have specified roles to play. The book also focuses on the Confucian heritage practices in Chinese societies, such as the emphasis on examinations, the contestations between discipline and guidance, and the role of class teachers in school guidance.